2015
DOI: 10.3892/br.2015.422
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MALAT1 in the peripheral whole blood of patients with lung cancer

Abstract: Abstract.A blood-based biomarker assay is a non-invasive way to screen that can identify lung cancer at an earlier stage to improve the clinical outcome. MALAT1 is a broadly expressed, long non-coding RNA in human tissues and is overexpressed in numerous human carcinomas. The potential of MALAT1 in the whole blood of lung cancer was evaluated. In the present study, blood samples of patients with lung cancer and healthy volunteers (controls) were recruited and analyzed by quantitative polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 19 publications
4
46
0
1
Order By: Relevance
“…Six studies with eight datasets were finally included in the meta‐analyses after a systematic search of the databases was performed. The identification process of the studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies with eight datasets were finally included in the meta‐analyses after a systematic search of the databases was performed. The identification process of the studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Because of minimal invasion and easy sample collection, serological biomarkers for lung cancer diagnosis or screening are of great interest . Several studies have recently evaluated long noncoding RNA MALAT1 expression in serum or plasma of NSCLC patients and discussed its diagnostic performance . However, due to limited statistical power caused by a small sample size, the findings of the publications were inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies reported expression of lncRNAs in whole blood samples, measured by RT-PCR or qRT-PCR. Two of the studies found that the expression of MALAT1 in whole blood samples was lower in patients diagnosed with NSCLC than in the rest of the population, in contrast to the upregulated expression of MALAT1 in the tissues of NSCLC patients [124,125]. Another study found elevated SCAL1 expression in the airways of smokers and several lung cancer cell lines [126].…”
Section: Circulating Noncoding Rnasmentioning
confidence: 99%
“…MALAT1 представляет собой перспективный диагностический биомаркер, обнаруживаемый в крови, для эффективного выявления рака легких. Одно исследование показало повышенные уровни экспрессии MALAT1 в цельной крови пациентов с метастатическим раком легкого [38].…”
Section: циркулирующие Incrnas как биомаркеры ракаunclassified